2007
DOI: 10.3766/jaaa.18.8.2
|View full text |Cite
|
Sign up to set email alerts
|

The Objective and Subjective Evaluation of Low-Frequency Expansion in Wide Dynamic Range Compression Hearing Instruments

Abstract: The effects of low-frequency expansion on the objective and subjective evaluation of four channel in-the-ear hearing instruments was investigated. Three expansion settings were programmed in each device: expansion off, expansion restricted to channel one, and expansion restricted to channels one and two. Objective evaluations were conducted in quiet (Connected Speech Test) and in noise (Hearing in Noise Test) with speech levels fixed at 40 dB SPL. Subjectively, each participant rated expansion satisfaction in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…T he results confirmed the first hypothesis: CV recognition decreased significantly for the high expansion kneepoint condition. These findings are consistent with previous studies that found reduced speech recognition with high kneepoints in all or some of the frequency channels (Walker et al, 1984;Plyler et al, 2005aPlyler et al, , 2005bLowery and Plyler, 2007;Plyler et al, 2007;Zakis and Wise, 2007). This was the first study to have used low-level kneepoints in all frequency channels.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…T he results confirmed the first hypothesis: CV recognition decreased significantly for the high expansion kneepoint condition. These findings are consistent with previous studies that found reduced speech recognition with high kneepoints in all or some of the frequency channels (Walker et al, 1984;Plyler et al, 2005aPlyler et al, , 2005bLowery and Plyler, 2007;Plyler et al, 2007;Zakis and Wise, 2007). This was the first study to have used low-level kneepoints in all frequency channels.…”
Section: Discussionsupporting
confidence: 92%
“…Methodology differences could account for the discrepancies. The studies that found a preference for expansion had subjects rate expansion while using undesirable stimuli, such as low-level noise situations (Plyler et al, 2005a;Plyler et al, 2006;Lowery and Plyler, 2007;Plyler et al, 2007). The studies that found a preference for linear amplification used desirable stimuli, such as speech or music (Walker et al, 1984;van Buuren et al, 1999;Lowery and Plyler, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies involving smoking and nonsmoking adults have demonstrated that the levels of transient evoked otoacoustic emissions (TEOAEs) were significantly lower in the smokers [17,18,19,20,21,22]. Given the emerging evidence of a relationship between primary tobacco smoking and hearing loss it is reasonable to postulate that a similar association exists between passive smoking and hearing loss.…”
Section: Resultsmentioning
confidence: 99%